The Effect of Iron Deficiency Anemia and Different Treatment Methods on DNA Damage: 8-hydroxy-2-deoxyguanosine Level - Agar, Buket Esen; Akarsu, Saadet; Aydin, Suleyman (Sage Publications Inc, 2021)
Ionic iron causes damages at the cellular level by forming free radicals. Reactive oxygen species lead to the formation of oxidative base damages in DNA. Among these forms the most common one and the one which has the best known mutagenity is 8-hydroxy-2 '-deoxyguanosine (8-OHdG). We aimed to determine iron deficiency anemia (IDA) and its different forms of treatments; probable oxidative damage on DNA by looking at the level of 8-OHdG. The patients were divided into 4 subgroups: Oral treatment (p.o.) group; Intramuscular treatment (i.m.) group; Intravenous treatment (i.v.) group; Healthy control group. Blood and urine samples were taken from all patients totally 4 times. 8-OHdG levels detected in blood and urine samples were compared with the control group. IDA and the treatment of it affect the level of 8-OHdG. p.o. therapy should be the top priority on children.
Keywords: iron deficiency anemia; treatment; 8-hydroxy-2 '-deoxyguanosine; oxidative damage; DNA damage